Análise das tensões em próteses implantossuportadas esplintadas, variando a localização dos implantes, pôntico e cantilever: estudo pelo método dos elementos finitos tridimensionais - Batista, Victor Eduardo de Souza [UNESP] (2015)
Objective: The aim of this study was to assess the stress/strain distribution on bone tissue and stress distribution in the abutments, implants and fixation screws, generated by occlusal force under three-unit fixed prostheses supported by two or three implants in the posterior maxilla, varying the location of the implants (straight-line and offset), using of bridge, and mesial and distal cantilever extension by 3D finite element methods. Material and Methods: Six 3-dimensional models were developed. Each model simulated a bone block (type IV) of posterior maxillary segment, with two or three external hexagon (HE) of 4.0 x 10 mm, supporting three-unit fixed prostheses, which: M1 - straight-line implants supporting single crowns; M2 - straight-line supporting three-unit splinted prosthesis; M3 - offset implant supporting three-unit splinted prosthesis; M4 - three-unit splinted prosthesis central bridge; M5 - three-unit splinted prosthesis mesial cantilever extension; M6 - three-unit splinted prosthesis distal cantilever extension. The applied forces were 400N axial and 200N oblique. The stress in the abutments, implants and fixation screws was plotted by von Mises' criteria. The stress and strain on cortical bone was plotted by maximum principal stress and microstrain criteria, respectively. Results: The splinting (M2 and M3) decreased the stress values in the fixation screws, mainly for M3. The decrease of implant number (M4, M5, M6) caused an unfavorable biomechanical behavior for analyzed structures. In situations of rehabilitations with two implants, the use of bridge (M4) showed stress and strain distribution more favorable for analyzed structures. Conclusion: The splitting was effective on stress decreasing...